Amplifying mitochondrial function rescues adult neurogenesis in a mouse model of Alzheimer's disease - Kevin Richetin; Manon Moulis; Aurélie Millet; Macarena S. Arràzola; Trinovita Andraini; Jennifer Hua; Noélie Davezac; Laurent Roybon; Pascale Belenguer; Marie-Christine Miquel; Claire Rampon (Neurobiology of Disease, 2017)
Adult hippocampal neurogenesis is strongly impaired in Alzheimer's disease (AD). In several mouse models of AD, it was shown that adult-born neurons exhibit reduced survival and altered synaptic integration due to a severe lack of dendritic spines. In the present work, using the APPxPS1 mouse model of AD, we reveal that this reduced number of spines is concomitant of a marked deficit in their neuronal mitochondrial content. Remarkably, we show that targeting the overexpression of the pro-neural transcription factor Neurod1 into APPxPS1 adult-born neurons restores not only their dendritic spine density, but also their mitochondrial content and the proportion of spines associated with mitochondria. Using primary neurons, a bona fide model of neuronal maturation, we identified that increases of mitochondrial respiration accompany the stimulating effect of Neurod1 overexpression on dendritic growth and spine formation. Reciprocally, pharmacologically impairing mitochondria prevented Neurod1-dependent trophic effects. Thus, since overexpression of Neurod1 into new neurons of APPxPS1 mice rescues spatial memory, our present data suggest that manipulating the mitochondrial system of adult-born hippocampal neurons provides neuronal plasticity to the AD brain. These findings open new avenues for far-reaching therapeutic implications towards neurodegenerative diseases associated with cognitive impairment.